The effect of work stressors on decision making - Bin Dajam, Hesham Saad; Alhazaymeh, Ahmed Saleh (Journal of Economic, Administrative and Legal Sciences, 2020)
The research aims to identify the role of work pressures on the decision-making process by applying to the administrative leaders at King Abdul-Aziz International Airport in Jeddah. The nature of the work, the ambiguity of the job role, social pressures), and the dependent variable, which is the decision-making process. The research concluded to provide a set of recommendations that serve the study population, namely: clarifying the roles and functions required of the staff of King Abdul-Aziz International Airport in Jeddah does not occur conflict between these functions, the distribution of job tasks between the employees or division of the task on the same worker at King Abdul Aziz Airport Jeddah International Airport, providing the appropriate environment of light and atmosphere suitable for workers at King Abdul-Aziz International Airport in Jeddah.